Four new species of the genus Casmara Walker, 1863 (Lepidoptera: Oecophoridae) from China - Wang, Shuxia; Zhang, Li; Wang, Jingjing (Zootaxa, 2012)
Four new species of the genus Casmara Walker are described based on specimens collected in China: C. quadrilatera sp.nov., C. acantha sp. nov., C. longiclavata sp. nov., and C. aduncata sp. nov. Illustrations of the adults and male genitalia are provided.